Enhancing Tendon Regeneration: Investigating the Impact of Topography on the Secretome of Adipose‐Derived Stem Cells - Qiuzi Long; Chuanquan Liu; Haotian Zheng; Mingyue Wang; Hanmei Liu; Yue Liu; Zhicheng Cao; Yuzhi Sun; Qingyun Mo; Ludvig J. Backman; Jialin Zhu; Lizhi Hu; et al. (Advanced Science)
Abstract Tendons are vital for maintaining integrity and movement, but current treatment options are insufficient for their regeneration after injuries. Previous studies have shown that the secretome from mesenchymal stem cells (MSCs) promoted tendon regeneration. However, limited studies have explored the impact of the physical microenvironment on the secretome's efficacy of MSCs. In this study, it is shown that the topographic orientation regulates the secretome of human adipose‐derived stem cells (ADSCs) and promotes tendon regeneration. Conditioned medium (CM) is collected from ADSCs cultured on the scaffolds with different topography. The results show that CM generated from aligned structure group has a potent effect in promoting cell migration and proliferation, tenogenic differentiation, macrophage polarization toward M2 phenotype, tendon structure and mechanical function recovery. Proteomic analysis revealed that the aligned structure can up‐regulate the secretion of Extracellular matrix (ECM) proteins while down‐regulate proinflammatory factors. This modulation activates the MAPK, GPCR and Integrin signaling pathways which may account for the enhanced effect on tendon regeneration. This study offers a promising and safer non‐cell‐based treatment option for tendon repair.